Effect of Salt Solution on the Mechanical Behaviours of Geopolymer Concrete under Dry-Wet Cycles - Zhiyu Tang; Nianchun Deng (Advances in Materials Science and Engineering)
Seawater splashing and frequent rainfall in the coastal area will often cause the concrete members to be affected by dry-wet cycles. In order to investigate the effect of salt solution on the mechanical behaviours of geopolymer concrete under dry-wet cycles, a series of tests on erosion of geopolymer concrete by three different salt solutions were carried out by using the mass loss rate, compressive strength, erosion resistance coefficient, and elastic modulus. The results show that, with the increase of dry-wet cycles, the mass of the specimen increases slightly at 20 dry-wet cycles and then decreases gradually. Then, the stress-strain curve of geopolymer concrete can be divided into three stages: linear growth stage, deceleration growth stage, and slow decline stage, which correspond to the elastic deformation stage, elastic-plastic deformation stage, and crushing stage, respectively. The overall trend of the stress-strain curve is similar under different dry-wet cycles, and the peak stress decreases with the increase of dry-cycle. The relationship between stress and strain of geopolymer concrete samples with different salt solutions is similar, while their strength characteristics have changed obviously. Furthermore, with the increase of dry-wet cycles, the compressive strength and the relative elastic modulus of geopolymer concrete gradually decrease, which reflects that sulfate erosion will lead to the strength loss of geopolymer concrete, causing its internal damage, thus having adverse effects on it. Different salt solutions have the great influence on the mass loss rate, compressive strength, erosion resistance coefficient, and elastic modulus of geopolymer concrete. In detail, the mixed salt solution erosion results in the greatest damage to geopolymer concrete and accelerates the damage. Chloride salt solution erosion causes middle damage to geopolymer concrete. Compared with the other two salt solutions, sulfate solution erosion leads to the least damage to geopolymer concrete and then sulfate has a certain inhibitory effect on the damage of geopolymer concrete. In addition, based on the test results, the constitutive model considering dry-wet cycles damage of salt solution is proposed, and the correctness is verified. This study has a good guiding value for geopolymer concrete engineering in coastal areas.